Coping with heat stress during match-play tennis: Does an individualised hydration regimen enhance performance and recovery?. (25th March 2014) - Périard, Julien D; Racinais, Sebastien; Knez, Wade L; Herrera, Christopher P; Christian, Ryan J; Girard, Olivier
Abstract : Objectives: To determine whether an individualised hydration regimen reduces thermal, physiological and perceptual strain during match-play tennis in the heat, and minimises alterations in neuromuscular function and physical performance postmatch and into recovery. Methods: 10 men undertook two matches for an effective playing time (ball in play) of 20 min (∼113 min) in ∼37°C and ∼33% RH conditions. Participants consumed fluids ad libitum during the first match (HOT) and followed a hydration regimen (HYD) in the second match based on undertaking play euhydrated, standardising sodium intake and minimising body mass losses. Results: HYD improved prematch urine specific gravity (1.013±0.006 vs 1.021±0.009 g/mL; p<0.05). Body mass losses (∼0.3%), fluid intake (∼2 L/h) and sweat rates (∼1.6 L/h) were similar between conditions. Core temperature was higher during the first 10 min of effective play in HOT (p<0.05), but increased similarly (∼39.3°C) on match completion. Heart rate was higher (∼11 bpm) throughout HOT (p<0.001). Thermal sensation was higher during the first 7.5 min of effective play in HOT (p<0.05). Postmatch knee extensor and plantar flexor strength losses, along with reductions in 15 m sprint time and repeated-sprint ability (p<0.05), were similar in both conditions, and were restored within 24 h. Conclusions: Both the hydration regimen and ad libitum fluid consumption allowed for minimal body mass losses (<1%). However, undertaking match-play in a euhydrated state attenuated thermal, physiological and perceptual strain. Maximal voluntary strength in the lower limbs and repeated-sprint ability deteriorated similarly in both conditions, but were restored within 24 h.